2018
DOI: 10.1073/pnas.1813365115
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic neuroprotection by coffee components eicosanoyl-5-hydroxytryptamide and caffeine in models of Parkinson's disease and DLB

Abstract: SignificanceCoffee consumption is linked with reduced risk of Parkinson’s disease (PD), and caffeine is generally believed to be the protective agent. However, several lines of evidence suggest the presence of additional compound(s) in coffee that can be protective as well. Here we show that eicosanoyl-5-hydroxytryptamide, which we purified from coffee as an agent that leads to enhanced enzymatic activity of the specific phosphatase PP2A that dephosphorylates the pathogenic protein α-synuclein, works in synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 64 publications
1
50
0
Order By: Relevance
“…In a human α-syn transgenic mouse model, using an EHT-enhanced diet, S129 phosphorylation was decreased, with concomitant reduction in α-syn aggregation and improvement of neuronal integrity leading to improved motor performance. Equivalent results were obtained on a similar WT α-syn transgenic mouse model, showing a synergistic effect of caffeine and EHT in enhancing PP2A activation [133]. These mechanisms of enhancing PP2A dephosphorylation of α-syn appear as promising therapeutic approaches, as they are safe and can be specific to α-syn through an allosteric activation, therefore avoiding the deleterious effects towards off-target proteins.…”
Section: Phosphorylationmentioning
confidence: 83%
See 1 more Smart Citation
“…In a human α-syn transgenic mouse model, using an EHT-enhanced diet, S129 phosphorylation was decreased, with concomitant reduction in α-syn aggregation and improvement of neuronal integrity leading to improved motor performance. Equivalent results were obtained on a similar WT α-syn transgenic mouse model, showing a synergistic effect of caffeine and EHT in enhancing PP2A activation [133]. These mechanisms of enhancing PP2A dephosphorylation of α-syn appear as promising therapeutic approaches, as they are safe and can be specific to α-syn through an allosteric activation, therefore avoiding the deleterious effects towards off-target proteins.…”
Section: Phosphorylationmentioning
confidence: 83%
“…Given the colocalization of α-syn with the lysosomal marker cathepsin D, the immunized mice could activate degradation pathways and thus eliminate α-syn more efficiently [203]. Following this study, another vaccination approach fused α-syn epitopes (α-syn [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] , α-syn [109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] , α-syn [126][127][128][129][130][131][132][133][134][135][136][137][138][139]…”
Section: Active Immunizationmentioning
confidence: 99%
“…The cytoprotective effect of Synucleozid was tested against α-synuclein PFFs. Human α-synuclein was expressed (79) and fibrillization was induced as previously described (80). SH-SY5Y cells were pretreated with Synucleozid (0.25 to 1 μM) for 24 h and challenged with 50 μg/mL α-synuclein PFFs for an additional 48 h in the presence of Synucleozid.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, recent studies have described a positive association between caffeine ingestion and improvement of exercise performance (Grgic et al, 2019) and a new mode of action of this compound at the mitochondrial level with beneficial effects on cardiovascular diseases (Ale-Agha et al, 2018). In addition to the potential role of caffeine as a protective agent on Parkinson's disease, Yan et al (2018) showed that the co-administration with eicosanoyl-5-hydroxytryptamide (another compound purified from coffee) enhanced the activity of a specific phosphatase that acts on α-synuclein, a characteristic pathogenic protein. However, another study (with more than 340,000 individuals) showed that those who consumed more than 6 cups of coffee a day had 22% more chances of developing cardiovascular diseases than nondrinkers (11%) and drinkers of decaffeinated coffee (7%) (Zhou and Hyppönen, 2019).…”
Section: Introductionmentioning
confidence: 99%